Фактори, які визначають ефективність процесу синхронізації технічної та фізичної підготовки плавців на етапі попередньої базової підготовки - Гращенко, Ж. В.; Hrashchenko, Zh. V.; Городня, М. О.; Horodnia, M. O.; Бєлий, С. П.; Bielyi, S. P. (Науковий часопис Українського державного університету імені Михайла Драгоманова. Серія 15: Науково-педагогічні проблеми фізичної культури (фізична культура і спорт). - 2024. - Вип. 4(177). - С. 33-36, 2024)
Обґрунтовано рангову структуру факторів, що визначають ефективність процесу синхронізації технічної та фізичної підготовки плавців на етапі попередньої базової підготовки. Цими факторами є: відповідність рівня фізичної підготовки до основних гідродинамічних параметрів техніки плавання; переважна спрямованість тренувального процесу на вдосконалення технічних особливостей вибраного способу плавання; вплив рівня розвитку спеціальних фізичних якостей на ефективність реалізації технічної майстерності. Менш значимими факторами є: відповідність засобів формування технічної та фізичної готовності до особливостей вікового розвитку організму юних плавців; стійкість технічних характеристик до впливу змагального навантаження у вибраному способі плавання; наявність функціональної бази перспективної реалізації індивідуальної техніки плавання. Виділені фактори впливають на ефективність процесу синхронізації технічної та фізичної підготовки юних плавців. Вони є методологічним основою розробки педагогічної технології, що регулює адаптивні процеси організму молодих плавців на етапі базової спортивної спеціалізації. Облік даних чинників необхідний розробки тренувальної програми формування інтегральної готовності спортсменів до змагальної діяльності.

The authors of the article justified the rank structure of factors that determine the effectiveness of the process of synchronization of technical and physical training of swimmers at the stage of preliminary basic training. The aim of the study to highlight the main factors that affect the effectiveness of the process of synchronization of technical and physical training of swimmers at the stage of preliminary basic training. The materials and methods served as an analysis and generalization of data from scientific and methodological and special literature; sociological research (questionnaire); mathematical statistics. The results. The structure of factors that determine the effectiveness of the process of synchronizing technical and physical training of swimmers at the stage of preliminary basic training are: compliance of the level of physical training with the main hydrodynamic parameters of swimming technique; the predominant focus of the training process on improving the technical features of the chosen swimming method; the influence of the level of development of special physical qualities on the effectiveness of the implementation of technical mastery Less significant factors are: conformity of the means of forming technical and physical readiness to the peculiarities of the age-related development of the organism of young swimmers; stability of technical characteristics to the influence of competitive load in the selected swimming method; the presence of a functional base for the prospective implementation of individual swimming techniques. Conclusions. The identified factors affect the effectiveness of the process of synchronizing technical and physical training of young swimmers. They are the methodological basis for the development of pedagogical technology that regulates the adaptive processes of the body of young swimmers at the stage of basic sports specialization. Accounting for these factors is necessary for the development of a training program for the formation of integral readiness of athletes for competitive activities.

Выделены основные факторы, влияющие на эффективность процесса технической и физической синхронизации подготовки пловцов на этапе предварительной базовой подготовки.
Factors that determine the effectiveness of the process of synchronization of technical and physical training of swimmers at the stage of preliminary basic training.
Keywords: фактори; плавці; етап попередньої базової підготовки; підвищення спортивної майстерності; синхронізація технічної та фізичної підготовки; підготовка плавців; factors; swimmers; stage of preliminary basic training; improvement of sportsmanship; synchronization of technical and physical training; training of swimmers; факторы; пловцы; этап предварительной базовой подготовки; повышение спортивного мастерства; синхронизация технической и физической подготовки; подготовка пловцов